Human immunodeficiency virus type-1 (HIV-1) continues to evolve in presence of broadly neutralizing antibodies more than ten years after infection. - Antoine Chaillon; Martine Braibant; Stéphane Hué; Samia Bencharif; David Enard; Alain Moreau; Assia Samri; Henri Agut; Francis Barin (PLoS ONE, 2012)
BACKGROUND: The evolution of HIV-1 and its immune escape to autologous neutralizing antibodies (Nabs) during the acute/early phases of infection have been analyzed in depth in many studies. In contrast, little is known about neither the long-term evolution of the virus in patients who developed broadly Nabs (bNabs) or the mechanism of escape in presence of these bNabs. RESULTS: We have studied the viral population infecting a long term non progressor HIV-1 infected patient who had developed broadly neutralizing antibodies toward all tier 2/3 viruses (6 clades) tested, 9 years after infection, and was then followed up over 7 years. The autologous neutralization titers of the sequential sera toward env variants representative of the viral population significantly increased during the follow-up period. The most resistant pseudotyped virus was identified at the last visit suggesting that it represented a late emerging escape variant. We identified 5 amino acids substitutions that appeared associated with escape to broadly neutralizing antibodies. They were V319I/S, R/K355T, R/W429G, Q460E and G/T463E, in V3, C3 and V5 regions. CONCLUSION: This study showed that HIV-1 may continue to evolve in presence of both broadly neutralizing antibodies and increasing autologous neutralizing activity more than 10 years post-infection.